Ancient roots of European linguistics: Apollonius Dyscolus on grammatical number - Wolanin, Hubert (Papers in Linguistics, 2025)
The aim of the paper is to show how Apollonius Dyscolus, the most prominent Greek grammarian of Antiquity, characterized the grammatical category of number and what issues related to this category he addressed in him treatise On Syntax. A thorough analysis of the treatise showed that the basic terminology used by the grammarian in reference to the category of number is to be found already in the Τέχνη γραμματική attributed to Dionysius Thrax, while Apollonius pays attention primarily to the semantics of this category and to syntactic issues. His interest in semantics is manifested in him regarding the number of verbs as an anaphoric and meaningless category, focusing on the elliptic nature of semantics of personal pronouns of the first and second person plural, pointing to the contextually determined phenomenon of expressing plurality by the article in singular, as well as – regarding certain nominal compounds – noticing some discrepancy between their grammatical number, determining the set of their referents, and the numeral aspect of what is implied by their lexical semantics. The syntactic matters related to grammatical number were discussed by Apollonius in the context of participles in plural used with collective nouns in singular, and verbal finite forms in singular used with neuter nouns in plural.